Independent Generation of Reactive Intermediates Leads to an Alternative Mechanism for Strand Damage Induced by Hole Transfer in Poly(dA-T) Sequences - Sun, Huabing (J Am Chem Soc, 2018)
Purine radical cations (dA•+ and dG•+) are the primary hole carriers of DNA hole migration owing to their favorable oxidation potential. Much less is known about the reactivity of higher energy pyrimidine radical cations. The thymidine radical cation (T•+) was produced at a defined position in DNA from a photochemical precursor for the first time. T•+ initiates hole transfer to dGGG triplets in DNA. Hole localization in a dGGG sequence accounts for ~26 % of T•+ formed under aerobic conditions in 9. Reduction to yield thymidine is also quantified. In poly(dA-T) sequences, 5-formyl-2′-deoxyuridine, which results from deprotonation from the C5-methyl group of T•+, is formed in low yield. This is inconsistent with mechanistic proposals concerning product formation from electron transfer in poly(dA-T) sequences, following hole injection by a photoexcited anthraquinone. Instead, the strand damage patterns observed in those studies, in which thymidine is oxidized, are reproduced by independent generation of 2′-deoxyadenosin-N6-yl radical (dA•). The original mechanism was disproven using hole injection by a photoexcited anthraquinone in DNA. Tandem lesion formation by dA• provides the basis for an alternative mechanism for thymidine oxidation ascribed to hole migration in poly(dA-T) sequences. Overall, these experiments indicate that the final products formed following DNA hole transfer in poly(dA-T) sequences do not result from deprotonation or hydration of T•+, but rather from deprotonation of the more stable dA•+, to form dA•, which produces tandem lesions in which 5′-flanking thymidines are oxidized.